DETENTION OF SNAKE VENOM PERUVIAN Bothrops ATROX AFFINITY COLUMN FOR OBTAINING SPECIFIC POISON - Sandoval P., G. A. (2011)
Has immobilized the snake venom of Bothrops atrox Peruvian to obtaining specific antibodies from the serum of immunized previously albino rabbits by affinity chromatography . Venom ( 100 mg ) was coupled to 1 g of BrCN - Sepharose 4B resin and packed into a chromatography column of 0.8 x 6.0 cm . This column was used for purification of specific antibodies from serum of New Zealand albino male rabbits ( 2 kg ) immunized with B. atrox venom . Serum ( 1 ml ) was applied to the column and protein fractions were eluted sequentially with 0.15 M NaCl , pH 6.0 buffer and 0.1 M glycine -HCl , pH 2.5 . Protein quantitation was performed by spectrophotometric methods . Immobilization of B. atrox venom gel yielded the affinity column to obtain anti- B antibodies . atrox , which were eluted with glycine -HCl buffer 0.1 M , pH 2.5 , recovering 100 mg of this antibody per mL serum. It is concluded that the use of Sepharose 4B column , BrCN yielded purified antibodies against B. atrox venom